Peran Growth Differentiation Factor-15 (GDF-15) sebagai Biomarker Prognostik Gagal Jantung: Literature Review - Brian; Iswandi Darwis; Eka Putri Rahmadhani; Intanri Kurniati (Medula, 2026)
Heart failure is a complex clinical syndrome with high morbidity and mortality, contributing to a substantial global health burden, including in Indonesia. Although conventional biomarkers such as BNP and NT-proBNP are well established for diagnosis and risk stratification, they have limitations in capturing the heterogeneous pathophysiology of heart failure. Growth Differentiation Factor-15 (GDF-15), a member of the TGF-β superfamily that increases in response to oxidative stress, inflammation, and myocardial ischemia, has emerged as a more comprehensive prognostic biomarker. This literature review examines clinical studies, prospective and retrospective cohorts, observational research, and meta-analyses evaluating the prognostic value of GDF-15 in acute and chronic heart failure. The synthesized evidence demonstrates that elevated GDF-15 levels consistently correlate with increased risks of mortality, rehospitalization, and disease progression. In addition, serial measurements of GDF-15 reflect therapeutic response, as failure of GDF-15 levels to decline is associated with poorer outcomes. Combining GDF-15 with other biomarkers, such as NT-proBNP, further enhances risk stratification accuracy compared with single-biomarker assessment. Based on current evidence, GDF-15 holds substantial potential as an independent and dynamic prognostic biomarker, supporting more precise risk assessment, disease monitoring, and clinical decision-making in patients with heart failure.